Approaches to α-amino acids via rearrangement to electron-deficient nitrogen: Beckmann and Hofmann rearrangements of appropriate carboxyl-protected substrates - Chandrasekhar, Sosale; Rao, V. Mohana (Beilstein Journal of Organic Chemistry, 2012)
The titled approaches were effected with various 2-substituted benzoylacetic acid oximes 3 (Beckmann) and 2-substituted malonamic acids 9 (Hofmann), their carboxyl groups being masked as a 2,4,10-trioxaadamantane unit (an orthoacetate). The oxime mesylates have been rearranged with basic Al2O3 in refluxing CHCl3, and the malonamic acids with phenyliodoso acetate and KOH/MeOH. Both routes are characterized by excellent overall yields. Structure confirmation of final products was conducted with X-ray diffraction in selected cases. The final N-benzoyl and N-(methoxycarbonyl) products are α-amino acids with both carboxyl and amino protection; hence, they are of great interest in peptide synthesis.
Keywords: amino acid; Beckmann rearrangement; Hofmann rearrangement; orthoacetate; trioxaadamantane